Peramalan Jumlah Kunjungan Wisatawan Menggunakan Model Generalized Space Time Autoregressive-Seemingly Unrelated Regression-Neural Network - Raihan Ayita Putri; Entit Puspita; Fitriani Agustina (Jurnal EurekaMatika, 2023)
The Generalized Space Time Autoregressive (GSTAR) model is a stationary space time model. One of the data that has a space time phenomenon is the number of tourist visits. The number of tourist visits is sometimes difficult to predict because it has patterns and characteristics that are difficult to identify. The model that considers non- linear elements is a neural network. The parameter estimation of the GSTAR model used is the Seemingly Unrelated Regression (SUR) model. This method is able to overcome the correlation between residuals every location. Data on the number of tourist visits in Magelang Regency is one of the time series data that has links between locations, has correlated residuals, and also nonlinear data patterns so that it can be modeled with the GSTAR-SUR-NN model. In this research, steps were taken to find out the best model and the results of forecasting the number of tourist visits at four locations in Magelang Regency, namely Telaga Bleder, Borobudur Temple, Bukit Rhema, and Mendut Temple with the GSTAR-SUR-NN model. The model chosen to predict the number of tourist visits at four tourist sites in Magelang Regency for the next 12 months is GSTAR(1,1)-SUR-NN(4,7,4) because this model produces better forecast results than the GSTAR( 1,1)-SUR.Keywords: GSTAR-SUR, Neural Network, Tourist Visit.AbstrakModel Generalized Space Time Autoregressive (GSTAR) adalah suatu model space time yang stasioner. Salah satu data yang memiliki fenomena space time adalah jumlah kunjungan wisatawan. Jumlah kunjungan wisatawan terkadang sulit untuk diprediksi karena memiliki pola dan karakteristik yang sulit untuk diidentifikasi. Model yang mempertimbangkan unsur non linier adalah Neural Network (NN). Pendugaan parameter model GSTAR yang digunakan adalah model Seemingly Unrelated Regression (SUR). Metode ini mampu mengatasi adanya korelasi antar residual setiap lokasi. Data jumlah kunjungan wisatawan di Kabupaten Magelang merupakan salah satu data runtun waktu yang memiliki keterkaitan antar lokasi, memiliki residual yang berkorelasi, dan juga pola data yang nonlinier sehingga dapat dimodelkan dengan model GSTAR-SUR-NN. Pada penelitian ini dilakukan beberapa tahapan untuk mengetahui model terbaik dan hasil peramalan jumlah kunjungan wisatawan pada empat lokasi di Kabupaten Magelang, yaitu Telaga Bleder, Candi Borobudur, Bukit Rhema, dan Candi Mendut dengan model GSTAR-SUR-NN. Model yang dipilih untuk meramalkan jumlah kunjungan wisatawan di empat tempat lokasi wisata di Kabupaten Magelang untuk 12 bulan mendatang adalah GSTAR(1,1)-SUR-NN(4,7,4) karena model ini menghasilkan hasil ramalan lebih baik daripada model GSTAR(1,1)-SUR.